Salmonella sp., Campylobacter sp., Escherichia coli. in the poultry sector, bacteria that put food safety at risk - Cala Delgado , Daniel Leonardo; Guzmán-Sànchez, Tannia Julied; Ferro-Villamizaro, Sergio Andrés; Díaz-Gélvez, Carlos Andrés; Bernal-Pérez, Miguel Ángel (Spei Domus, 2022)
Topic and scope: the implications of bacterium as external factors within food safety create effects that put the safety of poultry meat foods at risk, the investigation of the main bacterium such as Salmonella sp, Campylobacter and E. coli are of utmost importance, because they contribute to the mitigation of these microorganisms during the production chain. Characteristics: A literary review of scientific articles was carried out, with the interest of compiling information on topics pertinent to poultry products, external agents, outbreaks related to chicken consumption and the most common current strategies that reduce infections in the population. Findings: a growth in the consumption of poultry meat, where the need arises to guarantee a control of possible points of infection in the different parts of the poultry meat manufacturing, for the latter it is evidence of the effectiveness of the use of antibiotics, prebiotics and probiotics as food sanitation mechanisms. Conclusion: despite the advances in the investigation of pathogens and process improvements in the different stages of production, infections related to the consumption of chicken meat still persist.
Keywords: safety; poultry; bacterium; consumption; public health